Factors that Influence the Self-Efficacy of Former Drug Addicts to Stop Using Drugs: A Scooping Review - Mohamad Fikriyanto H. Kilo; Megah Andriany; Nur Setiawati Dewi (Indonesian Journal of Global Health Research, 2025)
A common problem among ex-drug users is relapse. Addiction in former drug users can be caused by self efficacy factors. This study aims to get a clear picture of the factors that influence the self-efficacy of former drug addicts to stop using drugs. Methods: Researchers used the scoping review method. The literature search was conducted using the search keywords "self efficacy" AND "relapse" OR "abstinence" AND "drugs". The databases used were Sciencedirect, Scopus, and Pubmed. The inclusion criteria were articles reviewed from publications in the last 5 years (2019-2023), articles that were in English, quantitative and/or qualitative research with a study population of former drug addicts who experienced relapse, and the full article was accessible. Stepwise screening was conducted and documented according to the PRISMA flowchart. Results: based on identification, there are 212 articles from search engines from sciencedirect, scopus, and pubmed. The final results obtained are 6 articles that match the criteria after going through the selection process. Self efficacy has many factors that can affect it such as negative emotions, apathy, shame and guilt, psychological, and delay factors predicting recurrence, as well as age. The researcher used the PEO (population, exposure, outcome) question format to find related research articles. Based on the analysis of 6 literatures, it can be concluded that former drug addicts have more serious challenges to stop using drugs.